A Humboldtian Approach to Mountain Conservation and Freshwater Ecosystem Services - Callisto, Marcos; Solar, Ricardo; Silveira, Fernando A. O.; Saito, Victor S.; Hughes, Robert M.; Fernandes, G. Wilson; Gonçalves-Júnior, José F.; Leitão, Rafael P.; Massara, Rodrigo L.; Macedo, Diego R.; Neves, Frederico S.; Alves, Carlos Bernardo M. (Frontiers in Environmental Science, 2019)
Complex environmental issues require solutions that cannot be achieved without integrating scientific disciplines and communicating science to people, decision-makers and stakeholders. Nevertheless, although Alexander von Humboldt gifted us with an approach to integrate knowledge across disciplines aiming to broadly understand environmental issues, our current scientific practice largely ignores that holistic approach. Here, we develop a conceptual framework for sustaining mountain integrity and securing their ecosystem services based on cross-disciplinary ideas. We used headwater systems located in tropical old mountains as an example of a meta-ecosystem because they are home to disproportional high levels of algae, invertebrate and microorganism species diversity and endemism as well as securing water availability and quality to nearly half of mankind. We also argue that the interplay between academia and other sectors of society should facilitate the permeability of scientific knowledge into policy- and decision-makers, which is a pivotal issue for improving natural resources management. We argue that the prioritization of tropical montane headwater systems is a feasible, desirable and strategic issue to be included in the global sustainability agenda. Failure to implement sustainable development goals in global mountains is likely to result in catastrophic events with harsh consequences for both humans and biodiversity.